2021
DOI: 10.3390/jrfm14120576
|View full text |Cite
|
Sign up to set email alerts
|

GARCH (1,1) Models and Analysis of Stock Market Turmoil during COVID-19 Outbreak in an Emerging and Developed Economy

Abstract: COVID-19 pandemic has led to uncertainties in the financial markets around the globe. The pandemic has caused volatilities in the financial market at varying magnitudes, in the emerging versus developed economy. To examine this phenomenon, this study investigates the impact of COVID-19 pandemic on stock market returns and volatility in an emerging economy, i.e., Indonesia, versus developed country, i.e., Hungary, using an event-study approach methodology utilizing GARCH (1,1) model. In this study, the Jakarta … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…To model stock market volatility for the entire study period, the GARCH model was applied. GARCH (1,1) was used because it is the most popular and robust model compared with other specifications (Brooks, 2008), it became a pioneer to model the volatility in the financial time series (Setiawan et al, 2021). Estimating the GARCH model requires stationary data; therefore, Phillips-Perron and augmented Dickey-Fuller unit root tests are used to check for stationarity.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To model stock market volatility for the entire study period, the GARCH model was applied. GARCH (1,1) was used because it is the most popular and robust model compared with other specifications (Brooks, 2008), it became a pioneer to model the volatility in the financial time series (Setiawan et al, 2021). Estimating the GARCH model requires stationary data; therefore, Phillips-Perron and augmented Dickey-Fuller unit root tests are used to check for stationarity.…”
Section: Methodsmentioning
confidence: 99%
“…To model stock market volatility for the entire study period, the GARCH model was applied. GARCH (1,1) was used because it is the most popular and robust model compared with other specifications (Brooks, 2008), it became a pioneer to model the volatility in the financial time series (Setiawan et al. , 2021).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The traditional econometric and statistical methods, including autoregressive integrated moving average (ARIMA) models ( 10 , 11 ), vector error correction model ( 12 ), generalized autoregressive conditional heteroscedasticity model ( 13 ), grey forecast model ( 14 ), exponential smoothing ( 15 ), causal analysis models, such as multiple linear regression ( 16 ), vector autoregression ( 17 ), threshold autoregression ( 18 , 19 ), are widely utilized to predict economic time series. These models have good interpretability and good performance based on linear assumptions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Zhang and Zhang (2020) showed that the GARCHbased option-pricing models are able to price the SPX one-month variance swap rate, that is, the CBOE Volatility Index (VIX) accurately. Setiawan et al (2021) used the GARCH(1, 1) model to analyze stock market turmoil during COVID-19 outbreak in an emerging and developed Economy.…”
Section: Introductionmentioning
confidence: 99%